A qualitative approach to the experience of patients from the diagnosis of cancer - Juliana Cândido Soares da Silva; Rayane Tavares da Silva; Josinaldo Furtado de Souza (Hospital de Clínicas de Itajubá, 2023)
Objective: to understand the experiences of cancer patients based on the diagnosis and the strategies adopted. Methods: this is a qualitative and transversal research, exploratory and descriptive. The sample consisted of 10 women with cancer assisted by a support association for cancer patients in João Pessoa/PB, selected by non-probabilistic convenience sampling. To collect data, a sociodemographic and health questionnaire was used, as well as a semi-structured interview based on the life history method. Sociodemographic data were analyzed using descriptive statistics (frequency and percentage), and data from the interview were analyzed using the Thematic Content Analysis technique proposed by Bardin. The average age of the women was 61.8 years. Four categories and 12 subcategories emerged. Results: the diagnosis of cancer caused negative impacts on the lives of patients and their families. Having a support network is an essential coping strategy used by patients due to the suffering caused by cancer. Conclusion: The importance of strategies for coping with the suffering of cancer patients was highlighted, especially concerning the support network, this being the most prominent category among all those found.